If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+6=2(2x+12)
We move all terms to the left:
6x+6-(2(2x+12))=0
We calculate terms in parentheses: -(2(2x+12)), so:We get rid of parentheses
2(2x+12)
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
6x-4x-24+6=0
We add all the numbers together, and all the variables
2x-18=0
We move all terms containing x to the left, all other terms to the right
2x=18
x=18/2
x=9
| 6-(x+-24)=18 | | x+2=3(-x-1) | | (3x+9)^5=2^5x | | 24r=0 | | 50x+2950x-15=60(50x+67) | | 2x+6=8 | | -13=4+b | | 1+7x+6=7 | | 57 =3x | | -11=k/5 | | 4/9+z=4 | | 9(1+2/3)=x+3 | | 1.8.88=4.44(x-7) | | x+16=2(2x-3) | | 18+12=r | | –2−6y=–5y | | (3y+8)+(3y+22)=180 | | A=p+ | | 3x/15=2/7 | | 3x+16=6x-6 | | .7h+14=8.4h | | 11/4*a=-1/2 | | 3x-2=4x+-x | | 7x-12-x²=0 | | 3x+41/2=-3+6x | | 8−9m=–10m | | 12/n=9/6 | | a4=28 | | -7-7x=6^3 | | (9x+1)=88 | | w÷7=14 | | 14x=723 |